BIAYA OVERHEAD PABRIK PEMBUATAN RUMAH TIPE 45/120 M2 PADA CV BHIMA HASTA SAMARINDA - TRIHARTANTO, TOTOK (EKONOMIA, 2013)
TOTOK TRIHARTANTO, Factory Overhead Making Home Type 45/120 M2 At Bhima CV Hasta Samarinda. Under the guidance of Mr. Jonathan and Mrs. Elfreda Robin.Overhead costs, the variables that occur in the July-August-September amounted to IDR 4,769,313.83 which means that the actual cost is less than its budget. Total difference in costThe difference consists of the sum of the variable costs and semi-variable overhead amounting to IDR 5,330,664.83 by a margin of fixed overhead cost of IDR 561,351.00. While the variable overhead costs that occurred in the period October - November-December amounted to IDR 3,348,794.05 which means that the actual cost is less than budgeted. The difference can be based on the sum of the difference in variable costs and semi-variable overhead for IDR 3,910,145. 05 with fixed overhead costs amounting IDR 561,351. 00 (Profitable).Based on the analysis and discussion it was concluded that the application of factory overhead costs of making the type 45/120 m2 July – August - September 2012 and October - November - December 2012, is the inefficiency of factory overhead costs. It can be concluded that the hypothesis has been put forward in the previous chapter authors, accepted.